McDougal Littell literature - Applebee, Arthur N.; Burke, Jim; Carnine, Douglas; Jackson, Yvette; Jimenez, Robert T.; Langer, Judith A.; Marzano, Robert J.; McCloskey, Mary Lou; Ogle, Donna M.; Olson, Carol Booth; Stack, Lydia; Tomlinson, Carol Ann (Illinois : McDougal Littell, 2009)
Provides standards based instruction in reading, writing, written and oral English language conventions, listening and speaking. Teaches students to identify, interpret, analyze, evaluate, make inferences, draw conclusions, compare and contrast, and classify.
Plot and conflict -- Character and point of view -- Setting and mood -- Theme and symbol -- Poetry -- Style, voice, and tone -- History, culture and the author -- Facts and information -- Argument and persuasion -- The power of research
Includes index.
Keywords: LITERATURE